Administrators’ perspectives on teachers breaking contract at international schools - Merchant, Stefan; Ingersoll, Marcea (Frontiers in Education, 2024)
This study on breaking contract at international schools provides insights from interviews with 13 international school administrators. Through an examination of the reasons for, and impacts of, breaking contract, five types of international school contract non-completion are identified. In addition to a typology for future studies of this phenomenon, the study outlines five impacts of contract non-completion and four key domains for school leaders to consider in relation to contract non-completion at international schools.